Can a city be sustainable? - Gardner, Gary T., 1958-; Prugh, Tom,; Renner, Michael, 1957- (State of the world library., 2016)
Cities are the world's future. Today, more than half of the global population lives in urban areas, and that number is expected to double by 2050. There is no question that cities are growing; the only debate is over how they will grow. Will we invest in the physical and social infrastructure necessary for livable, equitable, and sustainable cities? In the latest edition of State of the World, the flagship publication of the Worldwatch Institute, experts from around the globe examine the core principles of sustainable urbanism and profile cities that are putting these principles into practice. From Portland, Oregon to Ahmedabad, India, local people are acting to improve their cities, even when national efforts are stalled. Issues examined range from the nitty-gritty of handling waste and developing public transportation to civic participation and navigating dysfunctional government. Throughout, readers discover the most pressing challenges facing communities and the most promising solutions currently being developed. The result is a snapshot of cities today and a vision for global urban sustainability tomorrow. -- Back cover.